(untitled) (Nóema, 2016)
How are we supposed to be showing what must not be either «preached» or «founded»? What does it mean to convert oneself from one way of life to another? May an ethics of «acceptation» signify something different from an ethics of «resignation»? The author of the article will try to offer an answer to these crucial questions for Wittgenstein’s reflexion on ‘form of life’ – key concept of his late philosophy, whose ambiguity has not been however removed so far – starting from its «extraordinary» resemblance to the methodological issue raised by the universe of religious belief.